Morals and Politics - Rybakovas, Vladas (Problemos, 1990)
The relation of morals to politics is discussed in the ontological, axiological, and sociological aspects. The principle antinomies of the two are pointed out, namely, that of liberty and obligation, that of individual will and common will, and that of person and society. Morals and politics are said to exist as relatively independent phenomena. That is why the unclear separation of the two is theoretically inconsistent and practically harmful. The author of the paper holds that the relative autonomy of the two phenomena as well as their interrelations to a great extent are rooted in the very contradictiveness of the social relations.